(untitled) (Journal of Governance and Development (JGD), 2015)
This paper will discuss the practice of social entrepreneurship in the waste bank or â€œbank sampahâ€ activity in Surabaya city and reveal its potential for social and economic empowerment for urban community. As the second largest city in Indonesia, Surabaya has faced serious problem deal with waste. Interestingly, the problem has prompted the emergence of a community initiative to engage resolve the problem by setting up waste bank in their neighborhood. This study uses primary and secondary data that collected by interview and observation. Data analysis use interactive model data analysis. Location of study in Jambangan and Kebraon village, Surabaya. This study found that social entrepreneurs activity on waste bank in surabaya can provide additional family income, encouraged the emergence of innovative and creative community, and increasing social capital for the community. This paper also review the important factors that determine the appearance of social entrepreneurship in urban communities.